Calf muscle functional deficit 1-year after Achilles tendon rupture repair surgery - Aleknavičiūtė-Ablonskė, Vaida; Skurvydas, Albertas; Juodžbalienė, Vilma; Balčiūnas, Sigitas (Social Welfare: Interdisciplinary Approach, 2016)
The primary muscles responsible for plantar flexion movement are soleus and gastrocnemius which connects to the calcaneus by the Achilles tendon. Achilles tendon rupture is managed most often with open surgical repair in which the affected limb is immobilized. Understanding the effects of long-term immobilization, how these lead to changes in the physiological properties of the calf muscles changes, may help to improve rehabilitation. Investigating the biomechanical behavior of the calf muscles may provide a better understanding of how the inferior material properties of a scarred Achilles tendon may influence the more global structural properties of the intact muscles
Keywords: Isokinetic muscle torque; triceps surae; electromyography